209 'Mali Matters' – Reflections on a global health leadership and quality improvement project to improve blood transfusion safety at maluti adventist hospital, Mapoteng, Lesotho. (16th November 2020) - Snead, Charlotte; Upton, Rebecca; Niaina, Simon; Luthango, Ellen
Abstract : Introduction: This report relates to a quality improvement (QI) project aiming to improve blood transfusion safety at Maluti Adventist Hospital (MAH), Lesotho. The project ran over 6 months, from August 2019 to January 2020. The project team consisted of nine local staff members and two UK doctors working through the NHS 'Improving Global Health through Leadership Development' (IGH) programme. Methods: To understand existing processes and identify areas for improvement, baseline data was gathered and a 'process mapping' meeting was held. Improvements were implemented using Plan-Do-Study-Act (PDSA) methodology. A QI committee involving key stakeholders met fortnightly to discuss project progress. Results: Interventions were varied but included introduction of a pre-transfusion bedside safety checklist and staff transfusion training via a sustainable video. Documentation of critical patient identifiers improved both on transfusion request forms and at transfusion initiation. Completion of the bedside safety checklist was 65.5% by three months. Knowledge scores improved following transfusion training. 77% of staff strongly agreed and 21% agreed that the training was useful. Importantly, team members from both organisations reflected on their personal learning and development through the experience. Discussion: Initial progress was promising. Further work is needed to improve allocation of unique patient identification numbers and the safety of laboratory blood grouping and cross-match procedures. Challenges included short-staffing and government hospital strikes; subsequently the Covid-19 pandemic has limited ongoing QI work since February 2020. This collaborative system-strengthening project provided varied, reciprocal learning experiences for individuals from both organisations, including skills in leadership, teamwork, teaching, QI methodology, communication and IT. We believe that active reflection is a vital tool in the evaluation of QI work carried out in resource-limited settings in partnership with overseas organisations. Our experiences will help to inform ongoing work at MAH and may be of interest to others conducting QI work in similar settings.